2019 IEEE Congress on Evolutionary Computation (CEC) 2019
DOI: 10.1109/cec.2019.8790124
|View full text |Cite
|
Sign up to set email alerts
|

A Memetic Approach to the Solution of Constrained Min-Max Problems

Abstract: This paper proposes a novel memetic algorithm for the solution of constrained min-max problems that derive from the optimal design of complex systems under worst-case conditions. In this context the maximisation of a quantity of interest over the space of uncertain variables is required to identify the worst-case scenario (or worst-case solution under uncertainty). An optimal design vector is then identified such that the worst-case value of the quantity of interest is minimised. In the most general case, both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…For more details about the method please refer to Refs. 12,13 For the evaluated optimal design solution d * A , the decomposition approach presented in Refs. 6,[9][10][11] has been applied to the ML-ENM in order to propagate uncertainty through the spacecraft model and reconstruct a good approximation of the belief curve with a fraction of the computational cost required for the exact one (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For more details about the method please refer to Refs. 12,13 For the evaluated optimal design solution d * A , the decomposition approach presented in Refs. 6,[9][10][11] has been applied to the ML-ENM in order to propagate uncertainty through the spacecraft model and reconstruct a good approximation of the belief curve with a fraction of the computational cost required for the exact one (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Then the system is optimised for robustness with the min-max algorithm. 12,13 Evidence Theory is applied to quantify uncertainty on the optimal solution. 6,[9][10][11] It is finally shown that the optimal solution at phase A is robust against the uncertainty in the next design phases.…”
Section: Introductionmentioning
confidence: 99%
“…Then the system is optimised for robustness with a min-max algorithm. 12,13 Evidence Theory is applied to quantify uncertainty on the optimal solution. 6,[9][10][11] It is finally shown that the optimal solution at phase A is robust against the uncertainty in the next design phases.…”
Section: Introductionmentioning
confidence: 99%
“…We use a graph representation to model the CEdS and the interaction of the subsystems and components under uncertainty [3]. This approach allows to have a holistic and coherent view of the entire system and design process as well as simplifying the communications between different actors that are involved.…”
Section: Introductionmentioning
confidence: 99%